Exit interviews from two randomised placebo-controlled phase 3 studies with caregivers of young children with autism spectrum disorder - Hawken, Natalia; Falissard, Bruno; Choquet, Carl; Francois, Clement; Tardu, Jean; Schmid, Ramona (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Autism spectrum disorder (ASD) is characterised by difficulty with social communication and restricted, repetitive patterns of behaviour. This study aimed to improve understanding of the ASD patient experience with the treatment (bumetanide) regarding the changes in core symptoms and to assess changes considered as meaningful. To achieve this, qualitative interviews were conducted with caregivers of patients in two phase 3 clinical trials (NCT03715153; NCT03715166) of a novel ASD treatment. Methods Caregivers were invited to participate in one interview after completion of the pivotal phase 3 study; for those of them who continued treatment after study completion, a second interview was held 3 months after trial completion. The interviews were conducted by qualitative researchers and followed a semi-structured interview guide. The interviews focused on patients’ ASD symptoms and their impact on their daily life before enrolment, and on any symptom changes patients experienced during the trial. Results Out of the 13 eligible patients’ caregivers, 11 were interviewed up to two times at clinical sites in the UK, Spain, and Italy. The caregivers reported impairments in a wide range of skills: deficits in communication and social interaction; restricted, repetitive patterns of behaviour, interests, or activities; and cognitive, emotional, and motor impairments. Compared to before the trial initiation, caregivers also reported improvements in the following domains: communication, interaction with others, cognition, aggression, emotions, repetitive movements, eating, and sleeping. Conclusion The exit interviews provided a rich source of qualitative data, allowing a deeper understanding of caregivers’ and patients’ experience of the disease and allowing us to understand what constitutes a meaningful change. These data also helped identify important experiences that may inform the patient-reported outcome measurement strategy for future trials in ASD.